A Highly Crystalline 2D Conjugated Metal–Organic Framework for Superior Sodium Storage - Yin, Jia‐Cheng; Lian, Xin; Zhang, Jinli; Li, Zhi‐Gang; Liu, Ming; Pang, Jiandong; Li, Wei; Xu, Yunhua; Li, Na; Bu, Xian‐He (Angewandte Chemie International Edition, 2025)
Two‐dimensional conjugated metal–organic frameworks (2D c ‐MOFs) have emerged as promising electrode materials for sodium‐ion batteries (SIBs). However, developing 2D c ‐MOFs with multiple redox‐active sites and well‐defined structures to enhance the performance of SIBs and elucidate the structure–property relationship remains challenging. Herein, a 2D c‐ MOF single crystal (Cu‐TBP) with dual active centers was synthesized using an octahydroxyl tetrabenzophenazine (8OH‐TBP) ligand. Three‐dimensional electron diffraction (3D ED) analysis reveals the atomic‐level crystal structure of Cu‐TBP, characterized by a planar 2D rhombus network and a unique slipped AA layer‐stacking. Cu‐TBP exhibits typical semiconducting behavior with a high electrical conductivity (7.69 × 10 −3 S m −1 at 298 K) and a low thermal activation energy. Owing to its abundant redox‐active sites and superb electrical conductivity, Cu‐TBP shows remarkable electrochemical performance as a SIB anode, achieving a high reversible capacity of 369.7 mAh g −1 at 0.25 A g −1 , exceptional rate capability, and extraordinary cyclability (82.6% capacity retention after 800 cycles at 0.25 A g −1 ). Experimental studies combined with theoretical calculations further elucidate the Na + storage mechanism.